2022
DOI: 10.1149/1945-7111/ac51f6
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Linear Range Cholesterol Detection Using Fe2O3 Nanoparticles Decorated ZnO Nanorods Based Electrolyte-Gated Transistor

Abstract: Electrolyte-gated transistor (EGT)-based biosensors are created with nanomaterials to harness the advantages of miniaturization and excellent sensing performance. A cholesterol EGT biosensor based on iron oxide (Fe2O3) nanoparticles decorated ZnO nanorods is proposed here. ZnO nanorods are directly grown on the seeded channel using a hydrothermal method, keeping in mind the stability of nanorods on the channel during biosensor measurements in an electrolyte. Most importantly, ZnO nanorods can be effectively gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The LOD was estimated to be 0.42 mM according to the 3S/N principle, which was consistent with or better than those of other methods in previous reports. 40,64,65 3.6.2. Fluorometric detection of cholesterol.…”
Section: Catalytic Mechanism Of Fe-cdsmentioning
confidence: 99%
“…The LOD was estimated to be 0.42 mM according to the 3S/N principle, which was consistent with or better than those of other methods in previous reports. 40,64,65 3.6.2. Fluorometric detection of cholesterol.…”
Section: Catalytic Mechanism Of Fe-cdsmentioning
confidence: 99%
“…and their nanocomposites (i.e., ZnO-CuO, ZnO-Au, ZnO-Fe 2 O 3 , ZnO-polyaniline, ZnO-MWCNTs, etc.) have been utilized for fabrication of electrochemical-based sensors (enzymatic/non-enzymatic) for detection of different biomolecules and for health sciences. Mainly, zinc oxide (ZnO) nanostructures have been employed in designing improved sensors due to their easy and cost-effective synthesis approach, high surface-to-volume ratio, and being easily modified with other metal/metal oxides. However, ZnO nanomaterial-based hybrid nanostructures are preferred nanomaterials for the fabrication of different sensing devices with enhanced sensing properties compared to only ZnO nanostructure-based sensors. For example, recently, Sideeq Bhat et al used hybrid nanostructures of Au-ZnO NRs for the fabrication of an electrochemical-based sensor . They reported enhanced electrochemical properties of Au nanoparticle-modified ZnO nanorods while detecting 5-hydroxymethylcytosine in genomic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al used a hybrid nanostructure of ZnO and CuO (ZnO-CuO) for designing a non-enzymatic glucose biosensor, where CuO showed enzyme-like activity and helped to detect glucose . In other reports, Ahmad et al, Ahn et al, and Khan et al used a hybrid nanostructure of ZnO-Fe 2 O 3 for nitrite, potassium, and cholesterol sensing, respectively. In these reports, ZnO surface modification enhanced the catalytic features by enhancing the surface area. Dhingra et al reported the interfacial interactions of ZnO and polyaniline nanocomposites for optical and ammonia sensing by using hybrid nanostructures of ZnO-polyaniline .…”
Section: Introductionmentioning
confidence: 99%
“…Today, ZnO is widely used to detect glucose [ 18 ], cholesterol [ 19 ], uric acid [ 20 ], leptospira [ 21 ], antigens [ 22 ], ascorbic acid [ 23 ], cancer cells [ 24 ], DNA [ 25 ], and various biomarkers [ 26 ]. This semiconductor material is widely used in gas sensors [ 27 ], for targeted delivery of anticancer drugs [ 28 ], and other applications [ 29 ].…”
Section: Introductionmentioning
confidence: 99%